Teknik Budidaya Hidroponik dengan Sistem Wick - Setya Wibowo, Agung; Nur Suprianto, Amelia; Elhasani Al-Iksan, Yusuf (Universitas Islam Balitar, 2022)
Counseling activities in hydroponic cultivation of the wick system are an effort to implement family food security programs, one of which is by utilizing existing yard land and can increase family income. The problem that exists until now in farmers and the community of Kaulon Village, Sutojayan District, Blitar Regency, is the lack of awareness in utilizing yard land, as the problem is the method that will be given, namely 1. providing counseling in the form of providing material with lectures on hydroponic cultivation and how to use yard land so that it can be used as additional income for exit 2. hands-on practice in manufacturing hydroponic wick systems. The results of the activity showed that the community and farmers had high enthusiasm in carrying out hydroponic cultivation of the wick system by utilizing yard land, as can be seen from the 30 invited participants who attended, 90% of participants actively asked questions and the discussion went well. In making hydroponics, participants were able to carry out activities well, ranging from material preparation, tool preparation, hydroponic making to planting vegetable crops.